2016
DOI: 10.1080/1331677x.2016.1197552
|View full text |Cite
|
Sign up to set email alerts
|

Examination of factors influencing employees’ adoption of mobile commerce and services in Turkey

Abstract: This study first reviews and discusses mobile technology issues from a global perspective, and then investigates the impact of demographic (gender, age, income), personal (ICT experience, work experience), and organisational (sector) factors related to employees on adopting mobile commerce (m-commerce) and mobile services (m-services). A survey is conducted among employees from government-and private-sector organisations for this purpose, assuming that this group plays an important role in helping to adopt new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 41 publications
(38 reference statements)
0
5
0
5
Order By: Relevance
“…In this context, the Educational level and preparation programs in using MHRS for staff will boost the staff performance through Task-Technology Fit (Ratna et al., 2018). Moreover, Akman and Rehan (2016) found a significant relationship between the personal income, the work position, and the perceived usefulness of adopting m-commerce and MHRS. Therefore, the following hypotheses are anticipated:…”
Section: Research Hypotheses Developmentmentioning
confidence: 89%
See 1 more Smart Citation
“…In this context, the Educational level and preparation programs in using MHRS for staff will boost the staff performance through Task-Technology Fit (Ratna et al., 2018). Moreover, Akman and Rehan (2016) found a significant relationship between the personal income, the work position, and the perceived usefulness of adopting m-commerce and MHRS. Therefore, the following hypotheses are anticipated:…”
Section: Research Hypotheses Developmentmentioning
confidence: 89%
“…Many studies have addressed the staff background characteristics such as age, gender, income, educational level, and work position in adopting and acknowledging the use of MHRS (Akman and Rehan, 2016). Also, researchers pointed to a considerable association between gender and age and when using m-commerce and mobile technology (Meso et al., 2005; Yang, 2005).…”
Section: Research Hypotheses Developmentmentioning
confidence: 99%
“…ISSN 2345-0282 (online) http://jssidoi.org/jesi/ 2021 Volume 8 Number 4 (June) https://doi.org/10. 9770/jesi.2021.8.4(3) related barriers in m-commerce (Hew 2017) is also being widely conducted, which stems, in particular, from the partial differences in the conditions of trust in this type of e-commerce (Groß 2016;Javaria et al, 2020) and the need for separate analyses for different markets, as they are characterized by different m-purchasing patterns (Cyr 2008;Zhang et al 2012;Akman & Rehan 2016).…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
“…Apart from the analysis of specific situational contexts, which can be different, the additional scientific knowledge brought by the current study concerns the specificity of the m-market in question. Several previous analyses have shown that the development of m-commerce in different countries follows different trajectories (Zhang, Zhung & Liu 2012;Akman & Rehan 2016;Chehabeddine, Tvaronavičienė, 2020). In particular, clear distinctions were identified in terms of factors conducive to the adaptation of m-commerce (m-user readiness to enter m-transaction) between countries classified as Western and Eastern cultures, although due to the specificities of the available data, these findings were made for markets which are quite advanced in the use of mcommerce (Zhang, Zhung & Liu 2012) and did not cover post-socialist countries for which there is little research (Zbuchea, Vătămănescu & Pînzaru 2015;Woźniak 2017;Woźniak & Zbuchea 2018); in particularstudies comparing data from Poland, Romania, and Ukraine.…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
“…Model dan pengembangan hipotesisnya meliputi: 1. Hipotesis 1 Penelitian yang dilakukan di China menemukan bahwa perbedaan jenis kelamin berpengaruh terhadap perilaku di tempat kerja (Akman & Rehan, 2016;Chullen et al, 2015). Sedangkan penelitian yang dilakukan di Israel menemukan bahwa jenis kelamin berpengaruh terhadap faktor-faktor yang mempengaruhi sikap, dimana pada laki-laki, norma subjektif dari lingkungan dan orang tua berpengaruh terdap sikap, sedangkan pada perempuan, hanya dipengaruhi oleh orang tua (Sasson & Mesch, 2016).…”
Section: Model Dan Pengembangan Hipotesisunclassified